2022
DOI: 10.1523/eneuro.0418-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Basal Forebrain Chemogenetic Inhibition Converts the Attentional Control Mode of Goal-Trackers to That of Sign-Trackers

Abstract: Sign tracking versus goal tracking in rats indicate vulnerability and resistance, respectively, to Pavlovian cue-evoked addictive drug taking and relapse. Here, we tested hypotheses predicting that the opponent cognitive-behavioral styles indexed by sign tracking versus goal tracking include variations in attentional performance which differentially depend on basal forebrain projection systems. Pavlovian Conditioned Approach (PCA) testing was used to identify male and female sign-trackers (STs) and goal-tracke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 112 publications
1
8
0
Order By: Relevance
“…This insignificant trend reflected that females were more likely to be classified as STs. Although a similar pattern was previously observed (Kucinski et al, 2022), it has not been consistently found (Pitchers et al, 2015), reflecting considerable variation in the sex-dependent distribution of these phenotypes across cohorts obtained from different vendors as well as from different breeding barriers from the same vendors, and associated genetic heterogeneity (Fitzpatrick et al, 2013;Gileta et al, 2022). Note that in Fig.…”
Section: Screening Of Sts and Gtssupporting
confidence: 78%
See 2 more Smart Citations
“…This insignificant trend reflected that females were more likely to be classified as STs. Although a similar pattern was previously observed (Kucinski et al, 2022), it has not been consistently found (Pitchers et al, 2015), reflecting considerable variation in the sex-dependent distribution of these phenotypes across cohorts obtained from different vendors as well as from different breeding barriers from the same vendors, and associated genetic heterogeneity (Fitzpatrick et al, 2013;Gileta et al, 2022). Note that in Fig.…”
Section: Screening Of Sts and Gtssupporting
confidence: 78%
“…The relatively poor attentional performance of STs, and the associated propensity for approaching and contacting a Pavlovian cocaine cue, were previously attributed to attenuated levels of cortical cholinergic signaling when compared with GTs (Paolone et al, 2013; Pitchers et al, 2017a; Pitchers et al, 2017b; Pitchers et al, 2018; Kucinski et al, 2022). Furthermore, a deficient translocation of CHTs, from intracellular domains into synaptosomal plasma membrane, was found to underly the dampened capacity of the cholinergic system in STs (Koshy Cherian et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although Wnt11 expression has been shown to enhance acetylcholine nicotinic receptor clustering in neuromuscular junctions (Messeant et al, 2017) it has heretofore not been identified in the CNS, so its relevance to the behaviors we examined is uncertain. Forebrain acetylcholine function has been identified as a major correlate differentiating sign- and goal-tracking (Paolone et al, 2013), where attentional top-down deficits in sign-trackers relative to goal-trackers appear to reflect attenuated cholinergic functioning in the basal forebrain (Kucinski et al, 2022; Paolone et al, 2013) involving choline transporter systems (Carmon et al, 2023). Further, work from our lab and others demonstrate that nicotinic receptor agonism facilitates sign-tracking (Overby et al, 2018; Palmatier et al, 2014; Palmatier et al, 2013; Versaggi et al, 2016), raising the intriguing possibility that central Wnt11 may be involved in regulating the sign-tracking phenotype via CNS acetylcholine modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were given vehicle and CNO on alternate days. Regarding potential off-target effects of clozapine (Gomez et al, 2017), we and others have previously consistently failed to detect effects of this dose of CNO in rats expressing the control vector, including in rats performing the CTTT, complex movement control tasks, or an operant sustained attention task (Jendryka et al, 2019; Avila et al, 2020; Kucinski et al, 2022). Given effective dose ranges of clozapine in rodents performing complex behavioral tasks (Martinez and Sarter, 2008), and given the proposed conversion rate of CNO to clozapine, an approximately 50-100-fold higher dose of clozapine would be required to produce significant effects (see also Mahler and Aston-Jones, 2018; Lawson et al, 2023).…”
Section: Methodsmentioning
confidence: 97%